Acta Physiologiae Plantarum - Wojtaszek, Przemyslaw; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Established in 1978, Acta Physiologiae Plantarum is an international journal publishing peer-reviewed articles on all facets of plant physiology at various levels of biological organization, ranging from relevant aspects in molecular and cell biology to biochemistry.
Keywords: Agriculture; Plant biochemistry; Plant anatomy; Plant development; Plant pathology; Plant Physiology; Plant Genetics and Genomics; Plant Biochemistry; Plant Pathology; Plant Anatomy/Development.; Agriculture